Review Article about Arduino Microcontroller Based Syringe Infusion Pump - Ramadhan, Mohammed Abdulaal; Ramadhan, Maher Mohammed; Hameed, Saad Najeh; Hasanain Kadhim Lafta Alkharsan; Omar Hadi Khudhair Abbas (American Journal of Botany and Bioengineering, 2025)
An infusion pump is a medical device used to deploy fluids, medications, or nutritious supplements into a patient’s body in regulated amounts. It is an automated device that mimics the working of a standard syringe, where a plunger is pushed in to introduce fluid and that plunger is pulled back for a withdraw. Syringe infusion pumps presently in use are configured in a way that can push a fluid only in a single user-controlled, set flow rate. Not all infusions of medications can occur in the same pace, as different drugs are used at different flow rates. There is also a possibility of human error while configuring and setting up the infusion pumps, which can lead to mal-formations or incomplete infusions. An infusion pump is a device that can introduce fluids into a patient’s body without the need of physician’s assistance. Infusion pumps can use standard syringes to draw any volume of fluid from any vial size, preserving the sterility of the fluids and retracting the syringe after infusion. It can infuse any amount of fluid into the patient after an account of time, which can be varied per case, unlike current infusion pumps that have a fixed flow rate. It has a bigger display interface for easy use and understanding by physicians for a quick read and set-up, and has the option of pre-installed patient profiles for even quicker set-up of the device. Standard syringes can be used to inject and infuse fluids in a regulated manner with minimal chances of error. The system can use any syringe size, any vial size, any administering position, any infusing timer, or any infusion volume. There are several types of infusion pumps ranging from simple, stand-alone devices, to complex, computer-controlled pumps. Stand-alone infusion pumps are used for pulse generator type syringe pumps. High and low speed infusion pumps are constructed using open source electronics with understanding of fluid dynamics. Safety infusion pumps and tubing infusion pumps are also available. Automated infusion pumps such as software-controlled infusion pumps and fluid delivery sensor-controlled infusion pumps are also used. Stepper motor controlled devices are made use of for heavy duty applications such as missal testing, but face issues of cost efficiency and a broad vigilance range.